Inclusão de professores de ciências na sociedade da aprendizagem : análise de um curso de formação (des)continuada - Mulinari, Mara Hombre (2013)
The continuing advance of technology, mainly in the field of Information and Communication Technologies ICT combined with new forms of searching and obtaining information and learning something new, lend support to the conception of a Learning Society, that in the educational context presents in three aspects related to the implementation of these technologies in the school: the included student (or not), the teacher in the process of inclusion (or not) and the digitalized school. Together with this structure, there is the issue of teacher s continuous education. In this perspective, this research investigates the use of ICT in science teaching by teachers participating in the continuous education course of the Project Science Education funded by the Ministry of Education and carried out in 2007 in partnership with CEFOCO/UFES and the Education Departments of 21 municipalities of the State of Espírito Santo. This study aims at understanding how the participation in this course may have contributed to the digital inclusion of the teachers and the inclusion of ICT in pedagogical activities as well as to characterize the process of continuous education done in the municipalities with the teachers and define possible guidelines based on this experience that may contribute to further courses. Thus, a qualitative research was developed, as a study case in a historical-organizational perspective, based on the analysis of documents produced during the course in 2007 and semi-structured interviews with the tutor-teachers in 2012. Data analysis was carried out using the technique of systemic networks associated to the content analysis. The results reveal that the investigated course for teacher s continuous education was the pioneer in the process of digital inclusion for some teachers and despite the difficulties faced in 2007 in the accomplishment of that course, the prospective character of this research reveals the success of that education action and show that the implementation of ICT in the educational context for pedagogical means is important and requires breaking old paradigms in education as well as the incorporation of new perspectives of teacher s work that may be acquired through continuous education